2007
DOI: 10.1152/jn.00433.2006
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Eye Field Contributions to Rapid Corrective Saccades

Abstract: . Visually guided movements can be inaccurate, especially if unexpected events occur while the movement is programmed. Often errors of gaze are corrected before external feedback can be processed. Evidence is presented from macaque monkey frontal eye field (FEF), a cortical area that selects visual targets, allocates attention, and programs saccadic eye movements, for a neural mechanism that can correct saccade errors before visual afferent or performance monitoring signals can register the error. Macaques per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 69 publications
(98 reference statements)
7
97
0
Order By: Relevance
“…These cells would be ideally suited to compute the postsaccadic correction, as they would directly encode the visual prediction error. In accordance with this view, Murthy et al (2007) found with a double-step task a link between FEF activity and the latency of "corrective saccades"-actually large (Ͼ10°) saccades that resemble our S2 saccades. Overall, it is likely that FEF plays a major role in the postsaccadic updating.…”
Section: Neural Bases Of the Postsaccadic Update Processsupporting
confidence: 86%
“…These cells would be ideally suited to compute the postsaccadic correction, as they would directly encode the visual prediction error. In accordance with this view, Murthy et al (2007) found with a double-step task a link between FEF activity and the latency of "corrective saccades"-actually large (Ͼ10°) saccades that resemble our S2 saccades. Overall, it is likely that FEF plays a major role in the postsaccadic updating.…”
Section: Neural Bases Of the Postsaccadic Update Processsupporting
confidence: 86%
“…The slope of the ISI vs. RPT is often used as an explicit measure of concurrent planning of sequential saccades (14)(15)(16)(17)(18). Such a measure of RPT, however, is absent in the context of a delayed saccade task in which the second saccade may be concurrently planned along with the first saccade at any point during the hold-time (i.e., the time between the presentation of the initial target and the disappearance of fixation spot).…”
Section: Resultsmentioning
confidence: 99%
“…Proactive control is defined as the modification of a plan or a decision based on previous experience and in anticipation of forthcoming task demands (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). It is distinct from reactive control, where an externally presented signal explicitly indicates the required change in plan (16)(17)(18). Evidence for the existence of proactive control largely derives from studies using the countermanding task, where performance has been found to be modulated on a trial-to-trial basis depending on the likely occurrence of a stop signal, independent of its actual presence (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations